Neuroinflammatory Dynamics Underlie Memory Impairments after Repeated Social Defeat - McKim, Daniel B. (J Neurosci, 2016)
Repeated social defeat (RSD) is a murine stressor that recapitulates key physiological, immunological, and behavioral alterations observed in humans exposed to chronic psychosocial stress. Psychosocial stress promotes prolonged behavioral adaptations that are associated with neuroinflammatory signaling and impaired neuroplasticity. Here, we show that RSD promoted hippocampal neuroinflammatory activation that was characterized by proinflammatory gene expression and by microglia activation and monocyte trafficking that was particularly pronounced within the caudal extent of the hippocampus. Because the hippocampus is a key area involved in neuroplasticity, behavior, and cognition, we hypothesize that stress-induced neuroinflammation impairs hippocampal neurogenesis and promotes cognitive and affective behavioral deficits. We show here that RSD caused transient impairments in spatial memory recall that resolved within 28 d. In assessment of neurogenesis, the number of proliferating neural progenitor cells (NPCs) and the number of young, developing neurons were not affected initially after RSD. Nonetheless, the neuronal differentiation of NPCs that proliferated during RSD was significantly impaired when examined 10 and 28 d later. In addition, social avoidance, a measure of depressive-like behavior associated with caudal hippocampal circuitry, persisted 28 d after RSD. Treatment with minocycline during RSD prevented both microglia activation and monocyte recruitment. Inhibition of this neuroinflammatory activation in turn prevented impairments in spatial memory after RSD but did not prevent deficits in neurogenesis nor did it prevent the persistence of social avoidance behavior. These findings show that neuroinflammatory activation after psychosocial stress impairs spatial memory performance independent of deficits in neurogenesis and social avoidance. SIGNIFICANCE STATEMENT Repeated exposure to stress alters the homeostatic environment of the brain, giving rise to various cognitive and mood disorders that impair everyday functioning and overall quality of life. The brain, previously thought of as an immune-privileged organ, is now known to communicate extensively with the peripheral immune system. This brain–body communication plays a significant role in various stress-induced inflammatory conditions, also characterized by psychological impairments. Findings from this study implicate neuroimmune activation rather than impaired neurogenesis in stress-induced cognitive deficits. This idea opens up possibilities for novel immune interventions in the treatment of cognitive and mood disturbances, while also adding to the complexity surrounding the functional implications of adult neurogenesis.